Synergistic removal of nitrate by a cellulose-degrading and denitrifying strain through iron loaded corn cobs filled biofilm reactor at low C/N ratio: Capability, enhancement and microbiome analysis. (February 2023) - Li, Jiawei; Ali, Amjad; Su, Junfeng; Huang, Tinglin; Zhai, Zhenyu; Xu, Liang
Graphical abstract: Highlights: Cellulose-degrading and denitrifying strain were used synergistically in bioractor. Synergism of two strains enhanced the denitrification capacity of biofilm reactor. Fe@MCC showed hydrolysis of cellulose and better carbon release performance. The Fe 2+ released by the loaded iron on Fe@MCC can be used by strain XL4. Microbial community analysis showed cooperative features among the strains. Abstract: Optimization of nitrate removal rate under low carbon-to-nitrogen ratio has always been one of the research hotspots. Biofilm reactor based on functional carrier and using interspecific synergic effect of strains provides an insight. In this study, iron-loaded corn cob was used as a functional carrier that can contribute to the cellulose degradation, iron cycling, and collaborative denitrification process of microorganisms. During biofilm reactor operation, the maximum nitrate removal efficiency was 99.30% and could reach 81.73% at no carbon source. Dissolved organic carbon and carrier characterization showed that strain ZY7 promoted the release of carbon source. The crystallinity of cellulose I and II in carrier of experimental group increased by 31.26% and decreased by 21.83%, respectively, in comparison to the control group. Microbial community showed the synergistic effect among different strains. The vitality and metabolic activity of the target microorganisms in bioreactor were increased through interspecific bacterial cooperation.